Influence of financial compensation, work stress and position promotion on performance regional financial agency officers - Ronal Regen; Intan Suri; Badri Ahmad; Helmi Gusmindra (Journal of Educational and Learning Studies, 2022)
The purpose of this study was to analyze the effect of financial compensation, work stress and job promotion on the performance of employees of the Sungai Penuh City Regional Finance Agency. This research is motivated by low performance, financial compensation that does not meet needs, regulations that do not support work, low employee motivation, employees feel dissatisfied with applicable regulations both related to work implementation and financial compensation, and low achievement results. performance of institutions and employees of the Regional Finance Agency of Sungai Penuh City. The research method with a quantitative approach with multiple linear regression method. Data collection techniques with questionnaires, observations and interviews. The respondents of this study were 40 employees of the Regional Finance Agency of Sungai Penuh City. The sampling method used the total sampling method where the entire population in this study was used as the research sample. Hypothesis testing was calculated using the IBM Statistical Package for Social Science (SPSS) version 24.0 program. The results of this study found that financial compensation has a significant effect on employee performance, work stress has a significant effect on performance, promotion has a significant effect on employee performance, from the ANOVA test the value of Fcount > Ftable or 6.305 > 3.180 with a significance level of 0.001 or 0.05, then financial compensation, job stress, promotion together have a significant effect on the performance of employees of the Regional Finance Agency of Sungai Penuh City.